A casebook on Chinese outbound investment : law, policy, and business / edited by Matthew S. Erie, University of Oxford. - Erie, Matthew S. (Cambridge University Press, 2025)
China remains one of the top capital exporters in the world, yet there is a paucity of reliable sources through which to assess Chinese corporate decision-making, the implementation of Chinese-financed and managed projects, and the socio-economic effects of those projects. The Casebook fills this gap by providing fifteen case studies written by experts and researchers, many from host states and who have first-hand knowledge of the transaction or dispute in question. Case studies are written primarily based on primary source material including transactional documents, interviews with stakeholders, laws and regulations, and case decisions. Educators in professional schools, including law, policy, and business, will find in the Casebook material to supplement class discussions pertaining to Chinese overseas investment, Chinese investment strategies, and the nature of the Chinese firm. This title is also available as open access on Cambridge Core.